Analisa Peran Pencegahan Maladministrasi Dalam Positioning Ombudsman Jangka Panjang - Ria Maya Sari; Rosdiana Rosdiana (Fakultas Hukum Universitas Balikpapan, 2021)
ABSTRACTThis article aims to analyze few issues, which are: the development of Indonesian Ombudsman’s model after its 21 years’ establishment, the comparison of Ombudsman’s roles and functions before and after the enactment of Ombudsman Regulation Number 41/2019 concerning the procedures to prevent the maladministration in public services delivery, the analysis of the extent of the prevention roles in Ombudsman’s long-term positioning, the potential challenges Ombudsman will deal in implementing its prevention roles which are based on the writer’s experiences of having been working in Ombudsman Representative Office of East Kalimantan, and the recommendation proposals to tackle such challenges. This paper uses explorative research with qualitative analysis method on various related literatures and academic researches in addition to combine the normative-empiric approach according to the relevant regulations and the writer’s experience as aforementioned. This article proposes a few recommendations, most importantly: the streghtening of the knowledge and data management’s function, the networks of media, as well as the political lobbies to Ombudsman’s strategic partners; the necessity of academic research related to Ombudsman’s SWOT analysis and the formation of Ombudsman’s policy roadmap; and for the long term, to incorporate the Ombudsman into the Constitution for its institutional reinforcement. Keywords: Knowledge; Maladministration; Prevention; Ombudsman; Public Services